Changes in cognitive load and effects on parameters of gait - Oh, Chorong; LaPointe, Leonard L. (Cogent psychology, 2017)
Reading or texting with a mobile phone while walking requires cognitive resource allocation and consequently induces changes in gait. Fifty-six young adults walked along the GAITRite© walkway under baseline, low-, and high-cognitive loads. Participants' Functional Ambulation Profile (FAP), velocity, and stride length decreased while double-support time increased under higher cognitive load. This result shows that during cognitively loaded multitasking conditions participants are unable to stabilize their gait. In addition, lower FAP scores across the conditions suggest an increased risk for future injurious falls. This study demonstrates that distracted walking using a mobile phone can affect several parameters of gait and it would be prudent to not read or text on a mobile phone while walking.